2007
DOI: 10.1111/j.1365-2478.2007.00654.x
|View full text |Cite
|
Sign up to set email alerts
|

Importance of borehole deviation surveys for monitoring of hydraulic fracturing treatments

Abstract: A B S T R A C TDuring seismic monitoring of hydraulic fracturing treatment, it is very common to ignore the deviations of the monitoring or treatment wells from their assumed positions. For example, a well is assumed to be perfectly vertical, but in fact, it deviates from verticality. This can lead to significant errors in the observed azimuth and other parameters of the monitored fracture-system geometry derived from microseismic event locations. For common hydraulic fracturing geometries, a 2 • deviation unc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 11 publications
(25 reference statements)
0
29
0
1
Order By: Relevance
“…An alternative explanation of stage-to-stage changes in velocity model calibration was offered by Bulant et al (2007) who pointed out that errors in deviation surveys of both treatment and monitoring boreholes may cause significant and systematic changes in velocity model calibration (resulting in systematic bias in locations of microseismic events, as explained above). They show that VTI parameters of up to 20% (i.e.…”
Section: Locationsmentioning
confidence: 97%
“…An alternative explanation of stage-to-stage changes in velocity model calibration was offered by Bulant et al (2007) who pointed out that errors in deviation surveys of both treatment and monitoring boreholes may cause significant and systematic changes in velocity model calibration (resulting in systematic bias in locations of microseismic events, as explained above). They show that VTI parameters of up to 20% (i.e.…”
Section: Locationsmentioning
confidence: 97%
“…Failure to account for uncertainty and the limitations of a survey can lead to overinterpretation or misinterpretation of results (Bulant et al . ). Velocity model building has a significant effect upon estimated event locations and errors (Grechka and Yaskevich ; Grechka and Heigl ).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, Reference [12] indicated that the prior knowledge of velocity structure can optimize the downhole geophone configuration within the available well geometry to provide a better location image. For accurate definition to the geophone placement and orientation in a vertical monitoring well, surveys including the deployment of a coil-tubing string charge in a nearby borehole are important [13]. It is a common practice in hydraulic fracturing jobs to use offset wells to install the microseismic monitoring array, but the treatment well can also be utilized for this purpose [14] with notable increase in the background noise resulting from sensors position close to the injection spot.…”
Section: Methodsmentioning
confidence: 99%